Approved antibacterial drugs in the last 10 years: from the bench to the clinic - Miguel García-Castro; Francisco Sarabia; Amelia Díaz-Morilla; Juan Manuel López-Romero (Exploration of Drug Science)
Bacterial infections constitute one of the major cases of primary medical incidences worldwide. Historically, the fight against bacterial infections in humans has been an ongoing battle, due to the ability of bacteria to adapt and to survive. Indeed, bacteria have developed various mechanisms of resistance against several therapeutic agents. Consequently, the scientific community is always interested in search of new therapeutic agents, which are able to efficiently kill resistant-bacterial strains. This article covers the most recent antibacterial molecules approved by the Food and Drugs Administration (FDA) and European Medicines Agency (EMA) from 2012 to 2022 and intends to focus on synthetic derivatives to give a pedagogical view, with the goal of highlighting the importance of organic synthesis to obtain greater efficacy. A focus will be made on studies describing the structure and activity of the organic molecules and their interactions with their respective biological targets.